Antibacterial and Antifungal Activity of Coccinia grandis Leaves’ Extracts against Fish Pathogens - G, Muthulakshmi; Neelanarayanan, P. (Asian Journal of Biological and Life Sciences, 2020)
Coccinia grandis is used in India and other parts of the world as a medicinal plant. In the present study an attempt was made to identify the presence of phytochemicals in the Aqueous, Ethanol, Methanol and Petroleum ether extracts of leaves of C. grandis. The qualitative Preliminary phytochemical present of study reveals that alkaloids, phenol, flavonoids, steroids, terpenoids, saponins, tannins, protein, carbohydrates, glycosides, oils, gums, resins and amino acid by adopting standard methods. In this study antibacterial and antifungal activity of leaves extracts of C. grandis were tested against five pathogenic bacterial strains such as Bacillus subtilis, Staphylococcus aureus, Psedomonas aurginia, Escherichia coli and Vibrio anguillarum by agar well diffusion method. C. grandis were tested against four pathogenic fungal strains such as Candida albicans, Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus. The ethanol leaves extracts of C. grandis demonstrated higher antibacterial activities against Vibrio anguillarum (31±1.00 mm) in 500 μl concentration. A higher antifungal effect was observed with the ethanol leaves extracts with an inhibitory halo of Aspergillus niger (30.33±1.53 mm) in 500 μl concentration.
Keywords: Coccinia grandis; Phytochemical screening; Antibacterial activity; Antifungal activity